Renal cell carcinoma in patients with end‐stage renal disease has favorable overall prognosis. (4th February 2014) - Shrewsberry, Adam B.; Osunkoya, Adeboye O.; Jiang, Kun; Westby, Ruth; Canter, Daniel; Pattaras, John; Turgeon, Nicole; Master, Viraj A.; Ogan, Kenneth
Abstract Patients with end‐stage renal disease (ESRD) demonstrate a greater risk for renal cell carcinoma (RCC) than the general population. This study compared pathological and clinical outcomes in patients with RCC with and without ESRD. Patients with ESRD who underwent nephrectomy and were found to have RCC at our institution since 1999 were identified. The control group was composed of patients from the general population with RCC. The primary outcome was risk of cancer recurrence. The study included 338 RCC patients: 84 with ESRD and 243 without ESRD. In the ESRD group, mean tumor size was smaller, there was decreased prevalence of advanced T category (>3), and the average Karakiewicz nomogram score was lower. ESRD was associated with decreased tumor recurrence and clear cell pathology. No patients with ESRD had metastatic disease. There was no difference in overall or cancer‐specific mortality between the ESRD and control groups. Patients with ESRD who develop RCC have a better prognosis compared to RCC in patients without ESRD, which is likely secondary to favorable histopathologic phenotype as well as the likelihood of early diagnosis. Thus, the delay between nephrectomy and renal transplantation may not be necessary, especially in patients with asymptomatic, low grade tumors.